RESEARCH ON THE LEVEL OF QUALITY OF PRESCHOOL EDUCATION AND THE DEVELOPMENT OF TRENDS IN INTERNATIONAL EXPERIENCE - Turg`unova, Fazilat; Rustamova Shahnoza Abdurahimovna (Журнал иностранных языков и лингвистики, 2023)
Our article discusses and analyzes preschool education systems abroad. Features and directions of preschool education are highlighted. In the countries studied, the main problems of preschool education systems were identified. Characteristics of the main types and programs of preschool educational institutions are given.